Carbon electrode obtained via pyrolysis of plasma-deposited parylene-C for electrochemical immunoassays. Issue 16 (25th July 2022) - Song, Zhiquan; Park, Jun-Hee; Kim, Hong-Rae; Lee, Ga-Yeon; Kang, Min-Jung; Kim, Moo-Hwan; Pyun, Jae-Chul
Abstract : In this study, parylene-C films from plasma deposition as well as thermal deposition were pyrolyzed to prepare a carbon electrode for application in electrochemical immunoassays. Abstract : In this study, parylene-C films from plasma deposition as well as thermal deposition were pyrolyzed to prepare a carbon electrode for application in electrochemical immunoassays. Plasma deposition could prepare parylene-C in a faster deposition rate and more precise control over the thickness in comparison with the conventional thermal deposition. To analyze the influence of the deposition method, the crystal and electronic structures of the pyrolyzed parylene-C films obtained via both deposition methods were compared using Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, and Raman spectroscopy. For application as a carbon electrode in immunoassays, the electrochemical properties of the pyrolyzed carbon films from two both deposition methods were analyzed, including the double layer capacitance (2.10 μF cm −2 for plasma deposition and 2.20 μF cm −2 for thermal deposition), the apparent electron transfer rate (approximately 1.1 × 10 −3 cm s −1 for both methods), and the electrochemical window (approximately −1.0 ∼ 2.1 V for both methods). Finally, the applicability of the pyrolyzed carbon electrode from parylene-C was demonstrated for the diagnosis of human hepatitis-C using various amperometric methods, such as cyclic voltammetry, chronoamperometry, square-wave voltammetry and differential pulse voltammetry.